Expanding Research on the School-to-Prison Pipeline: Examining the Relationships between Suspension, Expulsion, and Recidivism among Justice-Involved Youth. (January 2022) - Novak, Abigail; Fagan, Abigail
Limited research has examined the associations between different forms of school exclusion and offending, and variation in these associations according to age of first exclusionary event, among justice-involved youth. Using data from the Pathways to Desistance Study, the current study examined the associations between suspension, expulsion, and recidivism and the association between age at first suspension/expulsion and recidivism. According to Cox proportional hazard models, both expulsion and frequency of suspension increased risk of recidivism; age at first suspension was not associated with recidivism, and youth who were first expelled in childhood were significantly less likely to recidivate than youth first expelled in adolescence. Results suggest juvenile justice and educational systems should provide collaborative services to better support justice-involved youth.